Increased Risk of Dementia Among Sleep-Related Movement Disorders: A Population-Based Longitudinal Study in Taiwan. Issue 51 (December 2015) - Lin, Chun-Chieh; Chou, Chung-Hsing; Fan, Yu-Ming; Yin, Jiu-Haw; Chung, Chi-Hsiang; Chien, Wu-Chien; Sung, Yueh-Feng; Tsai, Chia-Kuang; Lin, Guan-Yu; Lin, Yu-Kai; Lee, Jiunn-Tay
Abstract : Abstract: Sleep-related movement disorders (SRMD) are sleep disorders. As poor sleep quality is associated with cognitive impairment, we hypothesized that SRMD patients were exposed to a great risk for developing dementia. The present study was aimed to retrospectively examine the association of SRMD and dementia risk. A retrospective longitudinal study was conducted using the data obtained from the Longitudinal Health Insurance Database (LHID) in Taiwan. The study cohort enrolled 604 patients with SRMD who were initially diagnosed and 2416 patients who were randomly selected and age/gender matched with the study group. SRMD, dementia, and other confounding factors were defined according to International Classification of Diseases Clinical Modification Codes. Cox proportional-hazards regressions were employed to examine adjusted hazard ratios (HR) after adjusting with confounding factors. Our data revealed that patients with SRMD had a 3.952 times (95% CI = 1.124–4.767) higher risk to develop all-cause dementia compared with individuals without SRMD. The results showed that SRMD patients aged 45 to 64 exhibited highest risk of developing all-cause dementia (HR: 5.320, 95% CI = 1.770–5.991), followed by patients age ≥65 (HR: 4.123, 95% CI = 2.066–6.972) and <45 (HR: 3.170, 95% CI = 1.050–4.128), respectively. Females with SRMD were at greater risk to develop all-cause dementia (HR: 4.372, 95% CI = 1.175–5.624). The impact of SRMD on dementia risk was progressively increased by various follow-up time intervals (<1 year, 1–2 years, and ≥2 years). The results suggest that SRMD is linked to an increased risk for dementia with gender-dependent and time-dependent characteristics.